2005
DOI: 10.1089/dna.2005.24.503
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antigenic Epitope Mapping of Immunodominant Region Amino Residues 510 to 672 on the Spike Protein of the Severe Acute Respiratory Syndrome Coronavirus

Abstract: The severe acute respiratory syndrome (SARS) is a newly emerging human infectious disease caused by the severe acute respiratory syndrome coronavirus (SARS-CoV). The spike (S) protein of SARS-CoV is a major virion structural protein. It plays an important role in the interaction with receptors and neutralizing antibodies. In this study, the S1 domain of the spike protein and three truncated fragments were expressed by fusion with GST in a pGEX-6p-1 vector. Western blot results demonstrated that the 510-672 fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Because the SARS-CoV S protein can induce neutralizing antibodies, it is a suitable candidate for developing vaccine and diagnostic applications. Our mapping results showed that fragments Se-e (aa 456-650), Sf-f (aa 600-800) and Sg-g (aa 750-1000), reacting with 70, 70 and 100% of patients' sera, respectively (Table 1), covered most potential epitopic regions reported elsewhere Greenough et al, 2005;He et al, 2004;Hua et al, 2005;Ren et al, 2003;Wang et al, 2005;Zhi et al, 2005). We also identified, for the first time, an additional, highly antigenic fragment Sb-b (aa 150-400), which was recognized by 70% of patients' sera.…”
Section: Discussionmentioning
confidence: 62%
“…Because the SARS-CoV S protein can induce neutralizing antibodies, it is a suitable candidate for developing vaccine and diagnostic applications. Our mapping results showed that fragments Se-e (aa 456-650), Sf-f (aa 600-800) and Sg-g (aa 750-1000), reacting with 70, 70 and 100% of patients' sera, respectively (Table 1), covered most potential epitopic regions reported elsewhere Greenough et al, 2005;He et al, 2004;Hua et al, 2005;Ren et al, 2003;Wang et al, 2005;Zhi et al, 2005). We also identified, for the first time, an additional, highly antigenic fragment Sb-b (aa 150-400), which was recognized by 70% of patients' sera.…”
Section: Discussionmentioning
confidence: 62%
“…Hence, identification of neutralization epitopes within S and M sequence may enable the design of epitope-based SARS vaccines [9]. A couple of immunodominant epitopes from S and M protein of SARS-CoV have been identified through online epitope predication software or epitope mapping technologies and used for potential vaccine targets and therapeutic reagents [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As the receptor binding site of SARS-CoV, S-RBD is the most likely target for neutralizing Abs against the virus. Several groups have mapped a number of B cell epitopes in, or around, the S-RBD region (Hu et al, 2005;Hua et al, 2004Hua et al, , 2005Lu et al, 2005;Wang et al, 2003), although the exact location and conformational structure of such epitopes remain to be clarified. Our previous results demonstrated that SARS patients mounted early and strong humoral responses against fragment 450-650 of the S protein (S450-650) (Zhao et al, 2005a(Zhao et al, , 2005b, which contains the β6, but not β5, strand of the S-RBM.…”
Section: Introductionmentioning
confidence: 99%